2007 IEEE International Conference on Microelectronic Systems Education (MSE'07) 2007
DOI: 10.1109/mse.2007.48
|View full text |Cite
|
Sign up to set email alerts
|

Hardware Security: Preparing Students for the Next Design Frontier

Abstract: Hardware security (HS) RationaleIn the 70's, area emerged as the dominant synthesis and design objective for integrated circuit (IC), in the '80s the objective was speed of execution, and in the 90's it became power. While all these objectives are still very important, security, privacy, and digital right management (DRM) arise as the most important metrics in many modern and emerging applications [7]. The paradigm shift toward DRM, security and privacy is not only due to the common impact of technology pus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The use of programmable SoC platforms for teaching has also been described in [9]. A number of courses have also been reported which specifically focus on hardware security, one of the earliest work in this area by Koushanfar , et al from rice university where they present a course fully dedicated to hardware security threats and potential countermeasures [10]. More recently in [11], the authors reported a 3‐day training course on hardware security for PhD students, which includes theoretical lectures and practical labs, the authors reported good students feedback which indicated high level of interest in this area.…”
Section: Comparison With Related Workmentioning
confidence: 99%
“…The use of programmable SoC platforms for teaching has also been described in [9]. A number of courses have also been reported which specifically focus on hardware security, one of the earliest work in this area by Koushanfar , et al from rice university where they present a course fully dedicated to hardware security threats and potential countermeasures [10]. More recently in [11], the authors reported a 3‐day training course on hardware security for PhD students, which includes theoretical lectures and practical labs, the authors reported good students feedback which indicated high level of interest in this area.…”
Section: Comparison With Related Workmentioning
confidence: 99%
“…In the seventies, the most important synthesis and design objective for ICs was the area reduction, in the eighties, the objective was execution speed, and in the nineties, the objective was power dissipation. Although the objectives mentioned earlier still exist in a lot of new applications, security, privacy, and Digital Right Management (DRM) have become among the most important objectives [6] [7].…”
Section: Introductionmentioning
confidence: 99%